APPLICATION OF THE "VENN DIAGRAM" METHOD IN TEACHING NUCLEAR TECHNOLOGY IN HIGHER EDUCATION INSTITUTIONS (Web of Teachers: Inderscience Research, 2025)
The Venn diagram method is a graphic organizer used to visually compare and contrast two or more concepts, emphasizing their similarities and differences. Its integration into lecture-based instruction within the discipline of nuclear technology holds significant potential for addressing contemporary pedagogical challenges. As a component of modern pedagogical technology, the Venn diagram method contributes meaningfully to enhancing educational quality by promoting learner-centered, outcome-oriented, and reproducible teaching practices. Unlike traditional didactic approaches, pedagogical technologies emphasize active student engagement, conceptual understanding, and the practical application of knowledge. This paper examines the pedagogical value of incorporating the Venn diagram method into lectures on nuclear technology, particularly in the context of medical applications such as computed tomography (CT), magnetic resonance imaging (MRI), and X-ray diagnostics. While this method has been employed in various disciplines—including language instruction, teacher education, mathematics, and physics—its use in nuclear technology education remains underexplored. The study presents an applied model for implementing the Venn diagram technique in specialized coursework, demonstrating its effectiveness in improving student comprehension and interdisciplinary integration.